Supramolecular lipid nanoparticles as delivery carriers for non-invasive cancer theranostics - Syeda Zunaira Bukhari; Kornelius Zeth; Maryam Iftikhar; Mubashar Rehman; Muhammad Usman Munir; Waheed S. Khan; Ayesha Ihsan (Elsevier, 2021)
Nanotheranostics is an emerging frontier of personalized medicine research particularly for cancer, which is the second leading cause of death. Supramolecular aspects in theranostics are quite allured to achieve more regulation and controlled features. Supramolecular nanotheranostics architecture is focused on engineering of modular supramolecular assemblies benefitting from their mutable and stimuli-responsive properties which confer an ultimate potential for the fabrication of unified innovative nanomedicines with controlled features. Amalgamation of supramolecular approaches to nano-based features further equip the potential of designing novel approaches to overcome limitations seen by the conventional theranostic strategies, for curing even the lethal diseases and endowing personalized therapeutics with optimistic prognosis, endorsing their clinical translation. Among many potential nanocarriers for theranostics, lipid nanoparticles (LNPs) have shown various promising advances in theranostics and their formulation can be tailored for several applications. Despite the great advancement in cancer nanotheranostics, there are still many challenges that need to be highlighted to fill the literature gap. For this purpose, herein, we have presented a systematic overview on the subject and proposed LNPs as the potential material to manage cancer via non-invasive approaches by highlighting the use of supramolecular approaches to make them robust for cancer theranostics. We have concluded the review by entailing the future perspectives of lipid nanotheranostics towards clinical translation.